Molecular Analysis Of Cyp21 Gene In Patients Presenting With Ambiguous Genitalia. - Fuziah, M Z; Yulia, K M; Sidek, M R; Ramli, S F; Isa, M N; Anida, A. Rus (2002)
Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive disorders of adrenal steroidogenesis.